PRINCIPLES OF MODULAR TEACHING TECHNOLOGY - X.Z.Axmedova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The fundamental reforms implemented in the field of education in our republic ultimately provide for the training of competitive personnel with knowledge and skills at the level of world requirements. The system of knowledge and skills learned from the experience of developed countries finds its creative reflection in the State educational standards, curricula and programs developed for the purpose of implementing these tasks. In this system, professional skills also have an important place with their importance and scope.